Integrating Human-Centered Design and the Agile Development Process for Safety and Mission Critical System Development. (September 2017) - Sebok, Angelia; Walters, Brett; Plott, Christopher
The Agile software development process offers many potential benefits, including a design approach that allows frequent customer input, rapid development of functionality, and the ability to identify and resolve potential misunderstandings in design requirements. This process has generally been highly successful and offered many benefits to the software development industry. It is being adopted by an ever-increasing number of industries and used for applications beyond software development, including hard ware development, training materials, and marketing materials, to name a few examples. This paper describes a project to examine the integration of Human-Centered Design principles with the Agile process, and evaluate the appropriateness of this integrated process for safety and mission critical systems design.